Clinical Perspective in Fieldwork - Kulkarni, P. D. (Journal of Engineering Education Transformations, 1990)
One of the objectives of the TTTl’s is to bring about changes in the Technician Education System : to improve class-room teaching by the teachers; to better curriculum management by the HOD; institutional management by the Principals; & State level educational planning & management by the Directorate.